Measuring the work function of the (100) plane of Iridium electron emitter by probe hole field electron emission microscope - Ismaiel Hashim, Khalil (Libyan Journal of Science &Technology, 2024)
The work described in this paper is a study to measure the work function of the 100 plane (Φ100) of the iridium field emitter surface (the tip). The study has been carried out using a field emission microscope with a probe hole in the centre of the screen, which permitted to examine the individual crystal planes of the tip surface. The work function was computed from the current–voltage data using Fowler–Nordheim equation and a computer program which incorporated a point throwing routine and calculated errors in the measured work function were generally found to be ±0.02 eV or less